Pengaruh DPR Dan NPM Terhadap ROE Pada Situasi Casa Rendah - Cliff Kohardinata; Luky Patricia Widianingsih; Jennifer Jennifer; Jevan Andreas Talahaturusun (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This study aims to examine the effect of the DPR (dividend payout ratio), NPM (Net profit Margin) on ROE (return to equity) in low CASA conditions. The research method used to examine the effect of DPR and NPM on ROE in banks with low CASA (Current Account Saving Account) Â is multiple linear regression method with a quantitative approach. The theory used is the bird-in-the-hand theory and the profit-margin theory. The bird-in-the-hand theory explains the tendency of investors to choose to receive dividends rather than capital gains. The profit-margin theory explains that the cause of business depression is the inability of entrepreneurs to earn income that exceeds expenses and continue the business without suffering losses and bankruptcy. The results of the study show that the DPR and NPM have a significant positive effect on ROE at banks with low CASA.